2005
DOI: 10.1093/ndt/gfh987
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of FX high flux vs standard high flux dialysis for homocysteine clearance

Abstract: Background. Cardiovascular disease is the major cause of death in the end-stage renal disease population. Novel risk factors such as homocysteine (Hcy) are of considerable interest in this group as hyperhomocysteinaemia is highly prevalent in the setting of renal impairment. Folic acid-vitamin B group therapies are only partially effective treatments. Hcy is highly protein-bound and thus poorly dialysed. Dialyzers with albumin-leaking properties have been shown to result in lowering of plasma Hcy. As the FX-cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Also, treatment with nocturnal haemodialysis is independently associated with lower tHcy levels before dialysis 27 . However, the use of FX‐class dialysers, which have a better clearance of larger uraemic toxins than standard high‐flux dialysers but are non‐albumin‐leaking, did not result in a clinically significant benefit with regard to improved predialysis concentrations of tHcy 28 …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Also, treatment with nocturnal haemodialysis is independently associated with lower tHcy levels before dialysis 27 . However, the use of FX‐class dialysers, which have a better clearance of larger uraemic toxins than standard high‐flux dialysers but are non‐albumin‐leaking, did not result in a clinically significant benefit with regard to improved predialysis concentrations of tHcy 28 …”
Section: Discussionmentioning
confidence: 96%
“…27 However, the use of FX-class dialysers, which have a better clearance of larger uraemic toxins than standard high-flux dialysers but are non-albumin-leaking, did not result in a clinically significant benefit with regard to improved predialysis concentrations of tHcy. 28 Although this is a non-randomized trial with a relatively small number of patients in the treatment groups, which are not balanced regarding age and time on dialysis, it can be summarized that blood concentrations of water-soluble vitamins are reduced by the dialysis procedure. The nature of the dialysis membranes, high-flux or low-flux, has no influence on washout of vitamins.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed studies on the potential clinical benefits, however, have Some studies have demonstrated a reduced CRP, oxidized LDL cholesterol and pentosidine levels, suggesting a reduction in inflammation and oxidative stress, but these were performed comparing high-flux to low-flux dialysers unlike our study which is comparing two different high-flux dialysers to each other [11,14,15] . Previous studies on the FX class of dialyser have demonstrated no significant change in serum homocysteine level, parameters of oxidative stress or inflammation compared to use of a HF80 dialyser [16,17] .…”
Section: Discussionmentioning
confidence: 81%
“…High-flux dialysers with high capacity to eliminate large uraemic substances, but without excessive leakage of useful proteins such as albumin, show a larger intradialytic hcy reduction rate, about 40% compared to 30% with low-flux membrane, but pre-dialysis hcy values are slightly, but not significantly, lower with high-flux membranes compared to low flux dialysers after 3 months of follow-up [37]. Advanced high-flux polysulphone dialysers with great clearance of larger uraemic toxins, but nonalbumin-leaking, do not improve hcy clearance compared to standard high-flux polysulphone membranes, confirming that the major part of uraemic toxins affecting hcy metabolism are protein-bound or have a molecular weight above 15000 Daltons [38]. Super-flux, albumin-leaking, dialysers improve pre-dialysis plasma hcy concentrations compared to both low and high-flux membranes, mainly by removing large molecular weight solutes able to affect the hcy metabolism [39,40,41].…”
Section: Is Hyperhomocysteinemia To Treat?mentioning
confidence: 83%